Preparation for interpersonal communication - Wolek, Francis W. (Journal of the American Society for Information Science, 1972)
This paper describes three methods used by engineers and scientists to enrich their understanding of a technical subject prior to an interpersonal communication. Professionals may: (a) store the information need in hopes of an accidental or working encounter with the required information (piggybacking), and/or (b) verify and extend their background by contact with friendly associates (friendly consultation), and/or (c) review the literature of the field which is peripheral to their own (professional peripheration). Factors which determine the methods used are proposed: the opportunity cost of time, the extent to which similar needs have been encountered before, and the breadth of the user's (problem). Implications for the management of R & D organizations concern the provision of peripheral literature, the development of skills involved in consultation, and the clarification of the organization's technical goals.